Faktor yang mempengaruhi terjadinya karies gigi pada anak down syndrome usia 6-12 tahun : a scoping review - Jordan; Dwimega, Arianne; Dian Rahmadini, Enrita (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Dental caries is the most common oral disease in children worldwide and has been considered the most important problem in the oral cavity. Children with Down Syndrome (DS) usually have impaired communication, cognitive, and motor development so that it can be an obstacle in maintaining oral health in children. Objectives: To determine the factors that influence the occurrence of dental caries in children with Down syndrome aged 6-12 years. Methods: Scoping review using the last 10 years of journals that can be accessed through Pubmed, EBSCO, and Google Scholar databases using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Results: From the three databases, we found 816 journals. Duplication filtering found 19 journals with the same title. Screening journals through abstracts obtained 125 journals. The entire journal was then screened for eligibility according to the inclusion and exclusion criteria and 6 journals were obtained that fit the criteria. Conclusion: Down syndrome (DS) children have a lower risk of dental caries due to an increase in salivary pH, salivary flow rate, and salivary electrolytes which cause conditions in the oral cavity to become alkaline. The role of parents in maintaining children's oral health is also very important in preventing dental caries in DS children.